Daylight-triggered Directional Water Transport Fabric Prepared with TiO2 Sol-gel Method (Journal of Fiber Bioengineering and Informatics, 2015)
To build directional water transport fabric, cotton knitting fabric was finished with TiO_2 sol by two\rmethods: padding and spray. After finishing, the fabrics were irradiated in a self-made UV light box,\rduring which the water contact angle and directional water transport ability were tested. It was found\rthat the fabrics's irradiated side turned from hydrophobic to superhydrophilic within 2 hours, and after\r2 hours's irradiation they would recover to hydrophobic within 2 hours. The fabric's directional water\rtransport ability increased with the extend of irradiation time. The sprayed fabric responded more\rquickly than the padded fabric and took less time to recover than the padded fabric. But the padded\rfabric had higher maximum one-way water transport capacity.
Keywords: Directional Water Transport; Reversible Wettability; Daylight Triggered; TiO_2 Nanosol